VD_FINDINFO HC / 2016 / 504 vom 27. April 2016 - VD Tribunal cantonal (2016)
ASSURANCE-VOL, PRÉTENTION FRAUDULEUSE ENVERS L'ASSUREUR | 40 LCA, 168 CPC (CH), 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 322 al. 1 CPC (CH)